Tunable delivery vehicles to screen local biologic release profiles - D'Angelo, Anthony D (My University, 2024)
Biologics represent an increasing percentage of approved therapies and have the potential for treating numerous diseases such as cancers. While drug delivery vehicles (DDV) are in development for circumventing the poor pharmacokinetic properties of biologics, these drugs must be released at suitable rates and durations, to prevent toxic effects and disease progression. The optimal release profile for many immunomodulating biologics remains elusive and requires significant time and resources in the development of DDVs and pre-clinical studies. To expedite the discovery of efficacious release profiles, a method was developed for screening DDVs that deliver biologics to tissue mimics at different release rates and durations, which allowed for the temporal evaluation of cancer growth or killing. The DDVs incorporated a tunable displacement affinity release (DAR) mechanism for protein biologics within multicellular embedded spheroids cultures. Interestingly, shorter release profiles with five-day release durations resulted in greater killing than longer (>14 day) release profiles, highlighting the need for release profile screening platforms.